Anthropogenic and environmental drivers shape diversity of naturalized plants across the Pacific. Issue 6 (19th March 2021) - Wohlwend, Michael R.; Craven, Dylan; Weigelt, Patrick; Seebens, Hanno; Winter, Marten; Kreft, Holger; Zurell, Damaris; Sarmento Cabral, Juliano; Essl, Franz; van Kleunen, Mark; Pergl, Jan; Pyšek, Petr; et al.
Abstract: Aim: The Pacific exhibits an exceptional number of naturalized plant species, but the drivers of this high diversity and the associated compositional patterns remain largely unknown. Here, we aim to (a) improve our understanding of introduction and establishment processes and (b) evaluate whether this information is sufficient to create scientific conservation tools, such as watchlists. Location: Islands in the Pacific Ocean, excluding larger islands such as New Zealand, Japan, the Philippines and Indonesia. Methods: We combined information from the most up‐to‐date data sources to quantify naturalized plant species richness and turnover across island groups and investigate the effects of anthropogenic, biogeographic and climate drivers on these patterns. In total, we found 2, 672 naturalized plant species across 481 islands and 50 island groups, with a total of 11, 074 records. Results: Most naturalized species were restricted to few island groups, and most island groups have a low number of naturalized species. Island groups with few naturalized species were characterized by a set of widespread naturalized species. Several plant families that contributed many naturalized species globally also did so in the Pacific, particularly Fabaceae and Poaceae . However, many families were significantly over‐ or under‐represented in the Pacific naturalized flora compared to other regions of the world. Naturalized species richness increased primarily with increased human activity and island altitude/area, whereas similarity between island groups in temperature along with richness differences was most important for beta diversity. Main conclusions: The distribution and richness of naturalized species can be explained by a small set of drivers. The Pacific region contains many naturalized plant species also naturalized in other regions in the world, but our results highlight key differences such as a stronger role of anthropogenic drivers in shaping diversity patterns. Our results establish a basis for predicting and preventing future naturalizations in a threatened biodiversity hotspot.